Pengaruh PDRB Sektor Industri Pengolahan Terhadap PDRB ADHK Kota Malang Tahun 2017-2023 - Faradilla Ayu Rahmadhini; Edy Suhartono (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Regional economic development aims to increase income and community welfare as measured by GRDP. High GRDP indicates good economic performance, with the industrial sector improving the quality of human resources. In Malang City, although the processing sector declined in 2020, several sub-sectors grew and are expected to increase in 2023. This study examines the impact of changes in GRDP on the performance of the processing industry and its contribution to the economy, especially related to economic fluctuations in 2020 and 2021. This study analyzes the relationship between GRDP and the performance of the processing industry in Malang City and its contribution to regional economic development from 2017-2023. Using secondary data from BPS, the methods used are simple linear regression and quantitative descriptive analysis. GRDP is interpreted as the added value of goods and services, while the processing industry involves the transformation of basic goods into finished goods, with analysis using Eviews 12. The processing industry in Malang City plays an important role in the economy, with 18 types of industries based on high production value. Data analysis from 2017 to 2023 shows a significant relationship between the processing industry and GRDP, with a positive regression coefficient and an R-squared value of 99.5%, indicating a large influence of the industry on GRDP. This study is also in line with previous findings in Kediri Regency. The processing industry has a significant influence on GRDP ADHK Malang City in 2017-2023, with a contribution of 99.5%. As much as 5% of the influence comes from other variables outside this study. The processing industry contributed 99.5% to GRDP ADHK Malang City in 2017-2023, while 5% was influenced by other factors. The study suggests that the Malang City Government focus on this sector through export industry incentives, access to financing, and HR training.